Design pattern mining for GIS application using graph matching techniques - Pande A.; Gupta M.; Tripathi A.K. (My University, 2025)
Design Pattern Detection is a part of many solutions to Software Engineering difficulties. It is a part of reengineering process and thus gives important information to the designer. Design Pattern existence improve the program understanding and software maintenance. With the help of these patterns specific design problem can be solved and object oriented design become more flexible and reusable. Hence a reliable design pattern mining is required. A GIS is an information system designed to work with data referenced by spatial / geographical coordinates. Here we are detecting design patterns so that it can be used as a conceptual tool to cope with recurrent problems appearing in the GIS domain. In this way, GIS applications can evolve smoothly, because maintenance is achieved by focusing on different concerns at different times. © 2010 IEEE.